Factors for the adoption of modular construction/off-site construction in Klang Valley Malaysia - Chen, Yao Yoon (2023)
In Malaysia, the adoption of modular construction/off-site construction is still low in the construction industry. This may be due to several reasons such as high capital costs, poor technical integration, lack of knowledge and expertise, as well as low market shares. Therefore, this research study aims to investigate the factors for the adoption of modular construction/off-site construction to achieve more efficient construction and sustainable construction goals. First of all, a questionnaire survey was used to obtain opinions from developer, consultant, and contractor firms in Klang Valley, Malaysia. The respondents were asked to rate a total of 18 factors of TOE framework to the modular construction/off-site construction adoption. The data collected from questionnaires survey were analysed by using mean ranking analysis and factor analysis. Besides that, the findings from mean ranking analysis show that “top management support”, “managerial support”, “relative advantage”, “perceived ease of use”, and “technological capability” are perceived as the top five adoption factors among the eighteen factors. Furthermore, the eighteen factors could be grouped into five underlying common components by factor analysis, namely component 1 – adoption intention, component 2 – organisational capability, component 3 – technology dependability, and component 4 – technology robustness. Due to little study has been conducted on Klang Valley, Malaysia. Hence, this study closes the knowledge gap by investigating the TOE framework and generating statistical correlations between the variables. Therefore, the findings of this study have the potential to close the theoretical gap related with modular construction/offsite building, which is currently seldom acknowledged, particularly in Malaysia's Klang Valley. Lastly, the findings can also help the industry practitioners to better understand the prioritising important factors for the adoption of modular construction/off-site construction in Klang Valley, Malaysia.